Effects of Zinc Supplementation on Laying Performance, Serum Chemistry and Zn Residue in Tibia Bone, Liver, Excreta and Egg Shell of Laying Hens - Idowu, O.M.O.; Ajuwon, R.O.; Oso, A.O.; Akinloye, O.A. (International Journal of Poultry Science, 2011)
The effect of different sources of Zinc (Zn) in the diets of laying birds was investigated in a 10 weeks trial. Diets were formulated to include Zinc Oxide (ZnO), Zinc Sulphate (ZnSO4), Zinc Carbonate (ZnCO3) and Zinc Proteinate (ZnP) in which Zn in each diet was supplied at 140 mgKg-1 diet. Responses measured included performance, some serum biochemistry, Zn residues in tibia bone, liver, excreta and egg shell. Significant (p<0.05) differences were recorded among the treatment means in final body weight, feed intake, egg production and feed conversion ratio. Birds fed control diet significantly (p<0.05) consumed more feed than the birds on ZnP and other inorganic Zn sources. Birds on ZnP supplemented diet recorded significantly (p<0.05) higher egg production, this was however similar to the group fed ZnSO4 supplemented diet. Egg qualities were not significantly (p>0.05) different due to Zn sources except HU values. Serum glucose, SGPT and creatinine concentrations did not vary (p>0.05) due to Zn sources while serum protein, uric acid, SGOT and serum Zn concentrations were consistently lowered (p<0.05) in the control group. Birds on ZnP supplemented diet showed marked significant (p<0.05) difference in the value of Zn residue in tibia bone, liver and excreta of the chickens. The values of the stress indicators were consistently more pronounced in the control group than birds on Zn supplemented diets. For better laying performance, higher Zn retention and alleviation of stress, 140 ppm of Zn in bioplex form (Zn proteinate) was recommended for laying chickens in the tropics.